Prevention of infant eczema by neonatal Bacillus Calmette‐Guérin vaccination: The MIS BAIR randomized controlled trial. Issue 3 (9th August 2021) - Pittet, Laure F.; Messina, Nicole L.; Gardiner, Kaya; Freyne, Bridget; Abruzzo, Veronica; Francis, Kate L.; Morrison, Clare; Zufferey, Christel; Vuillermin, Peter; Allen, Katrina J.; Ponsonby, Anne‐Louise; Robins‐Browne, Roy; et al.
Abstract: Background: Bacille Calmette‐Guérin (BCG) vaccine could play a role in counteracting the rising prevalence of atopic diseases, through its beneficial off‐target effects. We aimed to determine whether neonatal BCG vaccination reduces the incidence of eczema in infants. Methods: Randomized controlled trial with 1272 infants allocated to receive BCG‐Denmark or no BCG at birth. The primary outcome was the 12‐month incidence of eczema based on 3‐monthly questionnaires. Eczema was also assessed at a 12‐month clinic visit. ClinicalTrial.gov: NCT01906853. Results: The 12‐month eczema incidence was 32.2% in the BCG group compared with 36.6% in the control group (adjusted risk difference (aRD) −4.3%, 95% CI −9.9% to 1.3%, multiple imputation model). In addition, comparing infants in the BCG group with the control group, 15.7% vs. 19.2% had eczema lesions at the 12‐month visit (aRD −3.5%, 95% CI −8.0% to 1.0%); 35.7% vs. 39.0% reported using topical steroids (aRD −3.3, 95% CI −9.2 to 2.7); and 7.3% vs. 10.2% had severe eczema scores (aRD −3.0%, 95% CI −8.8% to 2.7%). In 344 high‐risk infants (two atopic parents), the 12‐month eczema incidence was 35.3% in the BCG group compared with 46.8% in the control group (aRD −11.5%, 95% CI −21.9% to −1.2%; number needed to treat 8.7, 95% CI 4.6 to 83.3). Conclusion: There is insufficient evidence to recommend neonatal BCG vaccination in all infants for the prevention of eczema in the first year of life; however, a modest beneficial effect was observed among high‐risk infants. A single dose of BCG‐Denmark soon after birth could reduce the incidence of eczema in infants with two atopic parents. Abstract : Prevention of infant eczema by neonatal bacille Calmette‐Guérin vaccination: the MIS BAIR randomised controlled trial. In this RCT, a modest reduction in the 12‐month cumulative incidence of eczema was observed in infants vaccinated with BCG‐Denmark at birth compared with non‐BCG‐vaccinated infants in the control group. This reduction was greater in high‐risk infants (two atopic parents). The risk difference in high‐risk infants was ‐11.5% (95% CI −21.9% to −1.2%) with a NNT of 8.7 (95% CI 4.6 to 83.3). Abbreviations: BCG, bacille Calmette‐Guérin; CI, confidence interval; NNT, number needed to treat; RCT, randomised controlled trial.